Kenmu : Go-Daigo's revolution - Goble, Andrew Edmund (Harvard East Asian monographs, 1996)
Although the short-lived Kenmu regime (1333-1336) of Japanese Emperor Go-Daigo is often seen as a doomed revanchist attempt to shore up the old aristocratic order, Andrew Edmund Goble here forcefully argues that the flamboyant Go-Daigo and his iconoclastic associates were seeking to overcome the old order and did, indeed, decisively move Japan into its medieval age. By birth, education, and circumstances, Go-Daigo should have been a weak, fatalistic bit player. Instead he was a bold actor who forced situations to his own benefit and led a rebellion that overthrew the Kamakura bakufu. He was a sexual and religious adventurer, a student of Chinese political theory, and a politician with an unprecedented knowledge of the various regions of Japan. Kenmu Go-Daigo's Revolution tells his extraordinary personal story vividly and sets the Kenmu polity against a broad backdrop of social economic, and intellectual change at a dynamic moment in Japanese history.